Experimental study on anode components optimization for direct glucose fuel cells. (1st June 2019) - Song, Bing-Ye; He, Yan; He, Ya-Ling; Huang, Dong; Zhang, Yu-Wen
Abstract: Membrane electrode assemblies, as the core component, mainly determine the overall performance of fuel cells. As a part of it, the anode electrode is vitally important for the mass transportation and electrochemical reaction. To gain a high cell performance, the structures of the anode electrode are designed by optimizing the component parameters of the micro-porous and catalyst layers. The effect of polytetrafluoroethylene (PTFE) content in anode micro-porous layer and catalyst loading in catalyst layer on electrode resistance and electrochemical performance are investigated. The current collection effect affected by the carbon loading of micro-porous layer is analyzed, and the influence of catalyst binder on the fuel electrolyte transportation performance has been explained from the aspects of microscopic morphology. The experimental results show that the resistance of anode micro-porous layer can be decreased significantly by loading carbon black powder and PTFE with optimal contents on the micro-porous layer. As compared with the I2 anion-ionomer, the fuel electrolyte transportation can be facilitated by applying PTFE-bonded anode catalyst layer due to the richer micro-pores and larger specific surface area. In addition, there is an optimal anode catalyst loading of 1.7 mgPd ·cm −2 to achieve the highest peak power density of 11.5 mW cm −2 at 60 °C. Highlights: With optimal 20 wt% PTFE loaded in MPL, the resistance can be largely decreased. An ultra-thin MPL with 0.3 mgC ·cm −2 can further improve the cell performance. PTFE, as the anode catalyst binder, gives a larger active surface area than I2. The highest PPD with the optimal catalyst loading of 1.7 mgPd ·cm −2 are obtained.